Estudio citológico de plantas autotetraploides de frijol (Phaseolus vulgaris) - Monge Serrano, F.; Moh, C.C. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
By treating the shoot apices of twenty young bean seedlings (Phaseolus vulgaris, 2n = 22) with 0.2% colchicine solution for 20 hours, an autotetraploid sector was obtained from a treated plant. Two seeds were produced from this sector, and the chromosome number of the radicles of these two seeds was cytologically identified as 4n = 44. As compared with the diploid, some degree of gigantism was observed in these two 4n plants. The plants, the leaves, the stomata and the pollen grains were larger than those of the diploid. The 4n plants also had a prolonged reproductive period. About 50% of the pollen grains of the 4n plant showed intense staining with lactophenol-anilin blue, while almost 100% of the pollen grains of the 2n plants showed intense staining. No cells with more than 10 or less than 5 quadrivalents were observed in the pollen mother cells (PMC) in the 4n plants. The average number of quadrivalents per PMC was 7.3 which indicates that an average of 66% of the chromosomes form quadrivalents. The formation of bivalents in the 4n plants occurred in pairs from groups of the four homologues. This explains the high frequency of PMCs with even numbers of bivalents. The frequency of PMCs with univalents was of the same order as that of PMCs with trivalents, suggesting that in the majority of cases, the production of a univalent was due to the formation of a trivalent from the four homologues.